Pemanfaatan Sampah Puntung Rokok Sebagai Pestisida Alami Dalam Membasmi Lalat Rumah (Musca Domestica) - Muntu, Ronny; La Taha, La Taha; Atfal, Bustanul (Jurusan Kesehatan Lingkungan Poltekkes Kemenkes Makassar, 2024)
Flies are one of the insects (insects) belonging to the order Diphtera, have a pair of membrane-shaped wings. Flies are also species that play a role in public health problems, namely as vectors of transmission of digestive tract diseases such as diarrhea, cholera, typhoid, dysentery, and others. This study aims to determine the ability of cigarette butts to kill house flies (Musca domestica). This type of research is experimental. The samples in this study were 120 house flies (Musca domestica) with 3 repetitions for 15 minutes. The results showed that at a dose of 100 g within 15 minutes after exposure, 5 dead house flies, 7 dead at a dose of 200 g, and 9 dead flies at a dose of 300 g. It was concluded that from the three doses used, the dose that was most effective in killing house flies was a dose of 300 g with 9 tails after 15 minutes of observation. So that people are advised to use cigarette butts as a natural pesticide. Keywords: Garbage, cigarette butts; house flies, natural pesticides